STUDENT-TEACHERS’s PERSPECTIVES OF PRACTICUM PRACTICES AND CHALLENGES - Diala Hamaidi; Ibrahim Al-Shara; Yousef Arouri; Ferial Abu Awwad (European Scientific Journal, ESJ, 2014)
This study aimed at investigating the student-teachers' perspectives of practicum experiences and challenges. The study included all studentteachers at the Faculty of Educational Sciences at the University of Jordan who enrolled in practicum/2 course in the second semester of the academic year 2012/2013. A quantitative questionnaire consisted of 41 items was administered on (71) student- teachers of early childhood education and classroom teacher majors. The findings of the study revealed that the participants have benefited from the practicum practices in the development of many teaching skills such as: the interaction and communication with students and classroom management skills. However, both classroom student-teachers and early childhood student-teachers highlighted certain common challenges they encountered during their practicum experience. Implications and future recommendations were discussed.